Kombinasi Constructed Wetland Dan Koagulasi Dalam Menurunkan Kadar BOD Dan TSS Air Limbah Domestik - Wahyuni Sahani; Andi Muh. Alfian (Direktorat Politeknik Kesehatan Makassar, 2024)
Domestic waste water is a very potential source of water pollution because it contains hazardous and toxic substances that are pathogenic and can cause health problems, so it needs to be treated before being discharged into water bodies. This study aims to determine the effect of a combination of constructed wetlands and coagulation in reducing BOD and TSS levels of domestic wastewater. This type of research is a quasi-experimental with a pretest-posttest control design, namely testing the samples before and after processing. The independent variable in this study is a combination of constructed wetlands and coagulation with the dependent variables namely BOD and TSS levels. The data were analyzed descriptively by looking at the differences in the decrease after going through the treatment on the processing media. The results showed a decrease in the average initial levels of BOD and TSS after treatment with a combination of constructed wetlands and coagulation, the average BOD level decreased to 12.3 mg/l (94.9%). Meanwhile, the average TSS level decreased to 1.6 mg/l (98.3%). It was concluded that research on combinations of constructed wetlands and coagulation had an effect on reducing BOD and TSS levels of domestic wastewater based on Regulation of the Minister of Environment of the Republic of Indonesia Number 68 of 2016 so that it was suggested to the public to use this treatment in treating domestic wastewater and for further research it is best to acclimatize water hyacinth plants first before use.